2012
DOI: 10.1152/ajpgi.00189.2011
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic development in the liver and the implications of the n-3 fatty acid supply

Abstract: Novak EM, Keller BO, Innis SM. Metabolic development in the liver and the implications of the n-3 fatty acid supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 51 publications
(57 reference statements)
1
14
0
Order By: Relevance
“…As early as 1956, Mellinkoff et al found that a diet that contained very few short-chain saturated fats and relatively abundant long-chain unsaturated fats could significantly reduce Leu and Val and increase Pro, Cys, Arg and Asp in plasma [15]. Dietary fatty acids, particularly n-3 fatty acids, can spare AAs for protein and peptide synthesis [16]. On the contrary, AAs, especially those containing sulfur, can also modulate lipid metabolism [17].…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1956, Mellinkoff et al found that a diet that contained very few short-chain saturated fats and relatively abundant long-chain unsaturated fats could significantly reduce Leu and Val and increase Pro, Cys, Arg and Asp in plasma [15]. Dietary fatty acids, particularly n-3 fatty acids, can spare AAs for protein and peptide synthesis [16]. On the contrary, AAs, especially those containing sulfur, can also modulate lipid metabolism [17].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, omega-3 polyunsaturated fatty acids (n-3 PUFAs) and genistein have evidence to support their intake as part of preventative maternal prenatal nutrition. Novak et al43 performed a study whereby two groups of dams were fed the same total amount of dietary fat, but the composition of dietary fats differed between the groups. Each received different fats but both had the same total amount of dietary fat.…”
Section: Management Of Nafld: Prenatal and Postnatal Present And Futurementioning
confidence: 99%
“…The fatty acid (FA) composition of human breast milk (HM) is receiving increased attention, as the developmental and molecular functions of individual FA present within HM are increasingly understood in infant health [1-3]. FA have a multitude of structural, energetic, and bioactive functions [4], and postnatal FA excesses and deficiencies can influence responses to the nutrient and hormone milieu during development (cell division or differentiation).…”
Section: Introductionmentioning
confidence: 99%